2010
DOI: 10.3390/ijms12010001
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Single-Chain Fragment Variable by an Interdomain Disulfide Bond and Its Effect on Antibody Affinity

Abstract: The interdomain instability of single-chain fragment variable (scFv) might result in intermolecular aggregation and loss of function. In the present study, we stabilized H4—an anti-aflatoxin B1 (AFB1) scFv—with an interdomain disulfide bond and studied the effect of the disulfide bond on antibody affinity. With homology modeling and molecular docking, we designed a scFv containing an interdomain disulfide bond between the residues H44 and L100. The stability of scFv (H4) increased from a GdnHCl50 of 2.4 M to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The study of scFv chemical denaturation has already been approached by other authors 17,41,42 and as it was reported, scFv stability depends on the intrinsic stability of their variable domains (V H and V L ) and on the interaction between them. 42 Indeed, it was demonstrated that slight changes in the structure of one of the scFv domains, can modify the unfolding profile of the whole antibody fragment. 17 In this context, it could be suggested that the interaction between hydrophobic scFv regions and TX may modify the complete antibody structural stability, favoring the total protein denaturation at low urea concentration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study of scFv chemical denaturation has already been approached by other authors 17,41,42 and as it was reported, scFv stability depends on the intrinsic stability of their variable domains (V H and V L ) and on the interaction between them. 42 Indeed, it was demonstrated that slight changes in the structure of one of the scFv domains, can modify the unfolding profile of the whole antibody fragment. 17 In this context, it could be suggested that the interaction between hydrophobic scFv regions and TX may modify the complete antibody structural stability, favoring the total protein denaturation at low urea concentration.…”
Section: Discussionmentioning
confidence: 96%
“…As far as the structural stability is concerned, it was observed that the chemical unfolding of scFv resulted to be a cooperative process and TX significantly affected the denaturation mechanism (Figure ). The study of scFv chemical denaturation has already been approached by other authors and as it was reported, scFv stability depends on the intrinsic stability of their variable domains ( V H and V L ) and on the interaction between them . Indeed, it was demonstrated that slight changes in the structure of one of the scFv domains, can modify the unfolding profile of the whole antibody fragment .…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the added complexities associated with multispecific analysis, disulfide bond scrambling is another major area where antibody fragments and/or multispecifics present unique challenges. These challenges are especially prominent in multispecifics, particularly those composed of scFvs, because they can also contain additional (engineered) intrachain disulfide bonds that promote domain pairing [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. Mispairing of disulfide bonds can result in complex mixtures and aggregates with reduced activity and/or potential immunogenicity.…”
Section: Physical and Chemical Stabilitymentioning
confidence: 99%
“…A common problem with scFv is the weak binding affinity for the V H – V L pair [ 71 ] which, in the absence of stabilizing constant domains, makes the molecule prone to dissociation and the formation of aggregates. Some solutions to this problem that have been explored include the selection of more stable scFv frameworks [ 21 ] or the engineering of cysteines for the formation of an intra-Fv disulfide bond that stabilizes the V H – V L interaction [ 72 ]. Seeking an alternative but related solution to the stability problem, Johnson et al designed a format called DART (Dual Affinity Re-Targeting proteins), which basically is a diabody where the chains contain engineered cysteine residues that allow formation of an inter-Fv disulfide bond [ 73 ] (Fig.…”
Section: Fragment-based Bispecific Antibodiesmentioning
confidence: 99%